From Gas to Cash : Policy Options for Transferring Resource Revenues to Citizens in Mozambique - World Bank (Washington, DC, 2015)
Mozambique has enjoyed strong economic growth but poverty levels are still unacceptably high. Mozambique is now in a transition period with an opportunity to plan for how resource revenues can contribute to poverty reduction and inclusive growth. Any policy to scale-up a cash transfer program will operate with a limited budget, meaning that decisions will need to be made on the optimal design choice in Mozambique. The objective of this policy note is to generate debate on implementing a scaled-up cash transfer in Mozambique’s future resource-rich environment, as part of a broader strategy to reduce poverty. The scope of this note is focused on distributing resource revenues through a scaled-up cash transfer program, and not the broader management of resource revenues. Section one discusses growth and poverty dynamics. Section two presents the existing social protection system. Section three discusses policy options for implementing a scaled-up cash transfer program using a simulation exercise to estimate poverty and welfare effects for a given fiscal envelope. Section four discusses how to address the risks of financing a scaled-up cash transfer program from resource revenues. Section five focuses on the practicalities of how the social protection system should be strengthened to implement scaled-up cash transfer program and the final section concludes.